Temporal dusty plasma afterglow: A review - Couëdel, Lénaïc (Frontiers in Physics, 2022)
In complex plasmas, dust particles are charged through their interactions with the electrons and the ions of the surrounding plasma. In low-temperature laboratory plasmas, dust particles most commonly acquire a negative charge. In particular, in a laboratory glow-discharge plasma, the typical charge for a micrometer-size grain generally attains a few thousands of electronic charges. Under stable discharge conditions, this large negative charge is relatively well characterised. However for unsteady discharge conditions, the charge can differ and even fluctuate. In particular, when the power source of the discharge is turned off, the charged species of the plasma diffuse away and recombine into neutral species: this is a temporal afterglow. When dust particles are present inside temporal afterglow, the diffusion of charged species and the plasma decay dynamics will be affected. Moreover, the dust particle charge will also evolve during the afterglow period. In the late afterglow, dust particles are known to keep residual charges. The value of these residual charges strongly depends on the ambipolar-to-free diffusion transition. In addition, the presence of a dc electric field, causing ions to drift through the neutral gas, has a strong influence on the final dust particle residual charges eventually leading to large positive residual charges. In this review article, the dynamics of temporal afterglow complex plasma is discussed. Experimental results and current theoretical model are presented. The basics of temporal afterglow modelling are also given.